Underpricing and Board Structures: An Investigation of Malaysian Initial Public Offerings (IPOs) - Puan Yatim (Asian Academy of Management Journal of Accounting and Finance, 2011)
Using firm-level corporate governance data for 385 IPO (initial public offering) firms that sought to be listed on Bursa Malaysia from 1999 to 2008, this study examines the relationship between board structures and IPO underpricing, a performance indicator unique to the IPO context. The study finds that there has been recently a reasonably high level of underpricing in the Malaysian IPO market. Contrary to the prediction of this study, the results indicate that dual leadership structure and board reputation (i.e., multiple board memberships) are positively and significantly associated with the extent of IPO underpricing. It appears that the separation of board chair and CEO positions signals low quality for the IPO firm. Because of the risky nature of IPO firms, investors tend to favour continuity in leadership. Directors who hold outside board memberships with other firms also have a negative effect on investors' assessments of firm quality. Potential investors feel that directors with numerous board seats are inclined to become distracted in which case monitoring intensity is likely to suffer. Other board variables, namely, board independence (i.e., board composition) and board size, do not significantly link to underpricing. Finally, the study finds that both firm size and the total number of risks factors disclosed are negatively and significantly related to underpricing. Overall, these results provide evidence supporting that good corporate governance practices are likely to help potential investors identify quality IPO firms.